Political breakthroughs in the trenches - Pauline Grosjean; Saumitra Jha; Michael Vlassopoulos; Yves Zenou (Rockwool Foundation Berlin (RFBerlin), 2025)
We show how exposure to partisan peers, under conditions requiring high stakes cooperation, can trigger the breakthrough of novel political beliefs. We exploit the largescale, exogenous assignment of soldiers from each of 34,947 French municipalities into line infantry regiments during World War I. We show that soldiers from poor, rural municipalities-where the novel redistributive message of the left had previously failed to penetrate-voted for the left by nearly 45% more after the war when exposed to left-wing partisans within their regiment. We provide evidence that these differences reflect persuasive information provision by both peers and officers in the trenches that proved particularly effective among those most likely to benefit from the redistributive policies of the left. In contrast, soldiers from neighboring municipalities that served with right-wing partisans are inoculated against the left, becoming moderate centrists instead.
Keywords: D74; N44; L14; 330; Political Persuasion; Transmission; War; Voting Behavior; Conflict; Peer Effects; France; World War I